Measuring corporate reputation in B2B markets: the corporate personality adapted scale - Sequeira, N.; Vinhas da Silva, R.; Ramos, M.; Syed Alwi, S. F. (IUP Journal of Knowledge Management, 2015)
In Business to Business markets, a wrong decision on choosing a business partner may harm the company’s ability to survive and thrive into the future. Stakeholder involvement in organizations and the complex set of interactions between stakeholders and the organization, expressed in formal and informal relationships and characterized by a wide array of experiences, impressions, facts, perceptions, beliefs and knowledge, all of these contribute in different measures to organizational reputation. The research was conducted at Brisa Innovation and Technology (BIT), a Portuguese company operating in an open innovation network environment. The aim was to ascertain the viability of adding a new dimension to the corporate personality scale. The study allowed for a step forward towards the assessment of the viability of using Davies et al.´s (2001) model, initially conceived and applied in B2C contexts for the purposes of measuring reputation in B2B markets. It aims to do so by proposing a new dimension, “Commitment”, which has been proven to be statistically robust and reliable and may be incorporated into the scale, for the particular scrutiny of B2B markets reputation.